2007
DOI: 10.1111/j.1556-4029.2007.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on: Elemental Analysis of Human Cremains Using ICP‐OES to Classify Legitimate and Contaminated Cremains. J Forensic Sci 2006;51(5):967–73.

Abstract: J Forensic Sci 2006;51(5):967-73. Sir:The authors of this study performed careful analysis by inductively coupled plasma-optical emission spectroscopy (ICP-OES), followed by variable cluster and principal component statistical analysis on the resulting data to distinguish between mixtures of concrete and cremains. The ICP analysis consisted of dissolution of samples followed by measurement of concentration of a suite of 21 elements, seven of which were subsequently removed from the study for various stated rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In previous research, metric analysis has been successful for identifying inconsistencies between a set of cremains and a decedent using equations that take into account aspects of the biological profile, such as sex, stature, and weight (2,5,11,14,16). In addition, chemical analysis can be used to characterize urn constituents to determine whether they represent osseous or nonosseous material and to identify possible evidence of commingling (3,4,7,8,10,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In previous research, metric analysis has been successful for identifying inconsistencies between a set of cremains and a decedent using equations that take into account aspects of the biological profile, such as sex, stature, and weight (2,5,11,14,16). In addition, chemical analysis can be used to characterize urn constituents to determine whether they represent osseous or nonosseous material and to identify possible evidence of commingling (3,4,7,8,10,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Several reports on the detection and analysis of chemical and biological warfare agents (CBWAs) were published . Studies describing the analysis of human cremains were also reported , including the use of LIBS for the analysis of soils, plants, and cremains and the analysis of teeth by using statistical analysis of 45 elements . LIBS was also used for the detection of chemical taggants placed on objects .…”
Section: Trace Evidencementioning
confidence: 99%